Pemilihan Strategi Pemasaran dan Prediksi Pangsa Pasar Produk Pakaian Batik Menggunakan Rantai Markov (Studi Kasus: Toko Putra Bengawan Kampung Batik Laweyan Solo) - Cucuk Nur Rosyidi; Fitriana Indah; Murman Budijanto (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
Competition in the business world becomes more intense, both in manufacturing and services. It requires manufacturers to constantly innovate and have new breakthroughs in business. Likewise, the batik industry which is one part of the business world, it will experience a business environment which is full of competition and the competition is expected to continue to rise. The purpose of this study is to select the best marketing strategy derived from the marketing mix and retail using pair wise comparisons, then determines a strategy for optimal market share using Markov Chain. The results showed that the optimal strategy is discounted price. From the results of the analysis, the batik consumers in Kampung Batik Laweyan sensitive to price cuts strategy that results in the maximum market share.